2021
DOI: 10.1007/s11365-021-00759-1
|View full text |Cite
|
Sign up to set email alerts
|

The rhythm of effective entrepreneurs’ decision-making process. The pathways of alertness scanning and search and cognitive style. A mediation model

Abstract: How can entrepreneurs be effective when making decisions? To enrich current research on entrepreneurship and cognition, the present study shows how alertness and decision making are closely related. Prompted by the scant attention that scholars have paid to the link between alertness and the pathways of entrepreneurs’ thought, it proposes that being alert by adequately scanning and searching for information is likely to increase decision-making effectiveness. Distinguishing between rational and intuitive cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 90 publications
5
10
0
Order By: Relevance
“…Cognitive style is the basic factor determining individual and organizational behavior (Kozhevnikov et al ., 2005). The current study found that the relationship between innovative cognitive style and entrepreneurial leadership is significantly positive; the relationship between adaptive cognitive style and entrepreneurial leadership is significantly negative, which is consistent with previous studies (Sassetti et al. , 2022; Chen et al.…”
Section: Discussionsupporting
confidence: 92%
“…Cognitive style is the basic factor determining individual and organizational behavior (Kozhevnikov et al ., 2005). The current study found that the relationship between innovative cognitive style and entrepreneurial leadership is significantly positive; the relationship between adaptive cognitive style and entrepreneurial leadership is significantly negative, which is consistent with previous studies (Sassetti et al. , 2022; Chen et al.…”
Section: Discussionsupporting
confidence: 92%
“…Short et al (2010) studied to distinguish the core features of opportunity discovery and creation theories to simply the knowledge constraints for effective business creation models, but they became unsuccessful, and the literature remained complex in this context. GDMSs became integral for individuals to start a business venture; indeed, our study also approved its significance related to business phenomena as many previous studies provided similar evidence (Krasniqi et al, 2019;Cristofaro et al, 2021;Sassetti et al, 2021). Our findings align with Henley et al (2017), who argued that entrepreneurial intention is more important than entrepreneurial, analytical understanding that individuals can adopt through social interaction.…”
Section: Discussionsupporting
confidence: 91%
“…The GDMSs authenticate the managerial tendency and individual intentions to start a business venture to develop innovation through the lens of opportunity creation theory ( Sassetti et al, 2021 ). The indirect interaction of social capital through entrepreneurial intentions significantly impacts GDMSs on opportunity creation and vice versa for opportunity discovery.…”
Section: Discussionmentioning
confidence: 97%
“…Thirteen articles used a multidimensional assessment; that is, these studies wanted to know the behavior of each dimension of EA, so they were separately evaluated (e.g., Edigbo, Ogbo, Onwe, Igwe & Okafor, 2021;Liang, 2019). Finally, four articles focused on only one dimension, specifically scanning and search, since they considered it to be the trigger for the process of identifying opportunities (e.g., Sassetti, Cavaliere & Lombardi, 2022).…”
Section: Measurement Of Entrepreneurial Alertnessmentioning
confidence: 99%